2021
DOI: 10.1016/j.yebeh.2021.107773
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions and attitudes regarding epilepsy and disease cost after implementation of a community-based epilepsy treatment program in onchocerciasis-endemic communities in the Democratic Republic of Congo

Abstract: Highlights A community-based epilepsy treatment program reduced misconceptions and stigma. Providing free antiepileptic drugs reduced the cost for the families considerably. Long-term effectiveness and sustainability of the program remains to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…18 However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub-Saharan Africa. 19,13,20 Studies in Ethiopia and the Kilimanjaro region of Tanzania have examined knowledge about, perception of, and experience with epilepsy in PWE, and both reported limited knowledge and many misconceptions. [21][22][23] Other research has shown that people with little awareness and knowledge about epilepsy tend to have negative attitudes toward PWE and misperceptions about the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub-Saharan Africa. 19,13,20 Studies in Ethiopia and the Kilimanjaro region of Tanzania have examined knowledge about, perception of, and experience with epilepsy in PWE, and both reported limited knowledge and many misconceptions. [21][22][23] Other research has shown that people with little awareness and knowledge about epilepsy tend to have negative attitudes toward PWE and misperceptions about the disease.…”
Section: Introductionmentioning
confidence: 99%
“…One study from Burkina Faso reported witchcraft as a cause of epilepsy 18 . However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub‐Saharan Africa 19,13,20 …”
Section: Introductionmentioning
confidence: 99%
“…Increasing the awareness about this association could contribute to reducing stigma toward PWE [33]. In an onchocerciasis-endemic region in Ituri, in the Democratic Republic of the Congo, a community-based epilepsy treatment program was able to cause a shift in the community perceptions and attitudes toward epilepsy [34]. Thanks to this program, most community members no longer believe that epilepsy is contagious, and acknowledge that this condition can be treated in local health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to this program, most community members no longer believe that epilepsy is contagious, and acknowledge that this condition can be treated in local health facilities. As a consequence, PWE and their families experience less epilepsy-related stigma and are less likely to consult traditional healers [34]. Increasing the awareness about OAE is also important to motivate people to take ivermectin and for community-directed distributors of ivermectin to increase their efforts to reach a maximum level of CDTI coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Limited epilepsy awareness in the DRC has bred misconceptions, stigmatizing the disease. Surveys in Ituri found many people believe epilepsy is hereditary, contagious, caused by spirits, or witchcraft 30,31 . This stigma impedes social integration, pursuing employment, education, and marriage 30 .…”
Section: Stigmamentioning
confidence: 99%